SISTEM INFORMASI TRANSPARANSI PENYALURAN MAKAN BERGIZI GRATIS DI LINGKUNGAN DESA SUNGAI LANDAI - Sarmadi, Sarmadi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: The free meal program is an initiative by the village government to improve community welfare, particularly for vulnerable groups such as the elderly, orphans, and low-income families. However, the distribution process, which is still carried out manually, often leads to various issues, including lack of transparency, inaccurate beneficiary data, and the absence of verifiable distribution documentation. This study aims to design a web-based transparency information system model for the distribution of free meals in Village X. The method used is the Waterfall system development model, which consists of analysis, design, implementation, and testing stages. The results of this research indicate that the proposed system is capable of improving beneficiary data accuracy, enhancing documentation flow in the distribution process, and providing transparency features such as public reports, daily monitoring, and automatic distribution summaries.Keywords: Information System, Transparency, Free Meal Program, Village X, Web.